2011
DOI: 10.3109/02688697.2011.626878
|View full text |Cite
|
Sign up to set email alerts
|

Oxford craniotomy infections database: A cost analysis of craniotomy infection

Abstract: We describe the process of establishing a large database for the investigation of craniotomy infection and the preliminary results of this database. The initial results have been used to generate a cost analysis for craniotomy infection. The craniotomy infections database prospectively registers craniotomy cases taking place in the John Radcliffe Hospital. In order to achieve this, each patient's details are registered at the time of operation and followed up to identify cases of infection. Infection was defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
54
2
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 9 publications
6
54
2
7
Order By: Relevance
“…Furthermore, others have reported rates of infection-related reoperations after craniotomy that vary between <1% and 4%. 26,27,36 Both operative groups in our study have an SSI rate that is within the upper half of the range mentioned above. Also, our infection-related reoperation rate after craniotomy is in the upper range of rates described in previous reports.…”
Section: Incidence Of Ssis In Neurosurgical Operations With Shared-resupporting
confidence: 63%
See 1 more Smart Citation
“…Furthermore, others have reported rates of infection-related reoperations after craniotomy that vary between <1% and 4%. 26,27,36 Both operative groups in our study have an SSI rate that is within the upper half of the range mentioned above. Also, our infection-related reoperation rate after craniotomy is in the upper range of rates described in previous reports.…”
Section: Incidence Of Ssis In Neurosurgical Operations With Shared-resupporting
confidence: 63%
“…Previous studies without specific inclusion of intraoperative MRI reported SSI rates after craniotomy that vary between 1% and 8% with CNS infection rates after transsphenoidal surgery varying between 1.6% and 10%. 19,[22][23][24][25][26][27][28][29][30][31][32][33][34][35] A study on complications in glioma surgery with use of a one-room ioMRI operating suite recently reported a 1.4% incidence of SSIs. Furthermore, others have reported rates of infection-related reoperations after craniotomy that vary between <1% and 4%.…”
Section: Incidence Of Ssis In Neurosurgical Operations With Shared-rementioning
confidence: 99%
“…Three studies assessed postoperative outcomes of SSIs after CRANI, but the investigators did not adjust for patients' preexisting conditions. 16,26,30 At the University of Iowa Hospitals and Clinics (UIHC), the SSI rates after CRANI procedures ranged from 2.6% (low risk) to 5.2% (high risk). We previously found that procedures begun before the skin antiseptic dried and procedures during which Gliadel wafers (Arbor Pharmaceuticals, Inc.) were implanted were associated with an increased risk of SSIs.…”
mentioning
confidence: 99%
“…[1][2][3] In neurosurgery, these consequences, although relatively infrequent, are often more extreme, commonly requiring admission, reoperation and/or prolonged intravenous antibiotic therapy. [4][5][6] Effective preoperative antisepsis is considered a key element in preventing SSIs. The two most commonly used antiseptic agents are chlorhexidine (CHG) and povidone-iodine (PVI).…”
mentioning
confidence: 99%